CCNE1 EXPRESSION AND CA-125 LEVELS IN HIGH GRADE SEROUS CARCINOMA OVARY AT MOHAMMAD HOESIN HOSPITAL PALEMBANG ; A SINGLE-INSTITUTION DESCRIPTIVE STUDY - Fitriani, Dianli; Wresnindyatsih; Susilawati (Fakultas Kedokteran Universitas Sriwijaya, 2025)
High grade serous carcinoma (HGSC) of the ovary is the dominant subtype causing death from ovarian cancer. CCNE1 amplification occurs in 20% of ovarian HGSC and is associated with recurrence after platinum chemotherapy. Assessment of CCNE1 expression can be a screening for CCNE1 amplification. Measurement of CA-125 levels is routinely used for treatment monitoring and recurrence of HGSC patients. This study aims to assess CCNE1 expression, demographic characteristics and CA-125 levels of ovarian HGSC patients. Of the 31 HGSC patients, the study subjects were dominated by patients aged >50 years (61.3%), clinical stage FIGO III (64.5%), CCNE1 overexpression (71%), preoperative CA-125 levels ≥500 U/ml (77.4%) and postchemotherapy CA-125 levels <35 U/ml (58.1%).